Android Based Agricultural E Commerce Application for Farmer Transactions: Aplikasi E-Commerce Pertanian Berbasis Android untuk Transaksi Petani - Daffa Fauzanrio Iswinarko; Dr. Hindarto S.Kom., M.T; Ade Eviyanti, S.Kom., M.kom; Azmuri Wahyu Azinar, ST., M.comp (Indonesian Journal of Innovation Studies, 2025)
General Background The advancement of mobile technology has enabled digital solutions to support economic activities, including agricultural product distribution. Specific Background Farmers often face challenges such as limited market access and dependency on intermediaries, which reduce their profit margins. Knowledge Gap Existing systems do not fully provide a direct and accessible platform for farmers to connect with consumers through mobile applications. Aims This study aims to design and develop an Android-based e-commerce application to facilitate agricultural product transactions between farmers and consumers. Results The system is developed using a prototype model and incorporates features such as product listing, transaction management, and user interaction interfaces supported by UML modeling including use case, activity, and class diagrams. The application enables users to access product information and perform transactions efficiently. Novelty The integration of mobile-based e-commerce with direct farmer-to-consumer interaction provides a practical solution to reduce dependency on intermediaries. Implications This system supports improved accessibility in agricultural markets and offers a digital platform for more efficient transaction processes. Keywords: Android Application, E Commerce, Agricultural Products, Mobile System, UML Modeling Key Findings Highlights Mobile platform supports direct interaction between producers and buyers System design follows structured modeling using multiple UML diagrams Transaction features allow efficient product access and ordering processes